Above‐ and Belowground Growth, Biomass, and Nitrogen Use in Maize and Reconstructed Prairie Cropping Systems. Issue 2 (1st March 2015) - Dietzel, Ranae; Jarchow, Meghann E.; Liebman, Matt
ABSTRACT: We studied temporal dynamics of above‐ and belowground growth and N use in three production systems: maize (C4 annual), reconstructed prairie (a mixture of perennial C3 and C4 species) and fertilized reconstructed prairie. Our objectives were to fill knowledge gaps about temporal patterns of growth (especially for roots), inform further experimental research, and provide quantitative datasets for modeling. A 2‐yr field study was conducted near Boone, IA, in which above‐ and belowground plant tissues were sampled repeatedly during each growing season ( n = 15 aboveground, n = 4 belowground). Dry weight and tissue N concentration were measured, and growth rates and N productivity were estimated. We found that maize produced more aboveground biomass (18.4 Mg/ha) with higher growth rates that peaked later in the season compared with the two prairie treatments (9.4–14.9 Mg/ha/year). Maize allocated a smaller proportion of its biomass belowground (10%) than both prairie treatments did (20–40%). Overall the N productivity ranged from 11 to 135 kg biomass kg –1 thermal unit –1 for maize and 34 to 344 kg biomass kg –1 thermal unit –1 for both prairie treatments. Our findings provide new, quantitative data that will be useful for predicting system‐level processes of annual and perennial crops evaluated for food and biofuel production.